1967
DOI: 10.1097/00132586-196704000-00034
|View full text |Cite
|
Sign up to set email alerts
|

Serial Acid-Base Determinations in Normal Premature and Full-Term Infants During the First 72 Hours of Life

Abstract: have made a serial survey beyond the first 24 hours. It therefore seemed worth while to study the acid-base status on the same infants serially at predetermined times over a period of 72 hours. No such published data are available for premature infants. The opportunity also presented itself to re-evaluate the role ofpH and Pco5 in infants with a respiratory frequency over 60/min. but without respiratory distress (Branning, 1942;Prod'hom et al., 1964. Material and Methods An unselected group of premature and fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

1967
1967
1968
1968

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 6 publications
(11 reference statements)
1
7
0
Order By: Relevance
“…The development of metabolic acidosis after 48-72 hours of age had been previously suspected (Malan et al, 1965) and is confirmed in this study. The 678 Pco2 (mm.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…The development of metabolic acidosis after 48-72 hours of age had been previously suspected (Malan et al, 1965) and is confirmed in this study. The 678 Pco2 (mm.…”
Section: Discussionsupporting
confidence: 85%
“…Group B: babies of gestation 34-36 weeks-19 Group C: babies of gestation over 36 weeks-1. Arterialized capillary blood was collected and acidbase values determined by means of the Astrup method as previously described (Malan et al, 1965).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…found by Bucci, Scalamandre, Savignoni, and Mendicini (1965) and of about 2 mEq/l. found by Malan, Evans, and Heese (1965). Chest x-ray films obtained in 6 of the TRD infants showed hyperaeration and, in 2 cases, the reticulo-granular pattern usually associated with RDS.…”
Section: Resultsmentioning
confidence: 89%
“…Four of the RDS infants subsequently died. None of the infants had clinical findings suggestive of aspiration syndrome (Schaffer, 1960), pneumothorax, or pneumomediastinum (Malan and Heese, 1966). S.E.…”
mentioning
confidence: 98%